2022
DOI: 10.1089/nat.2021.0089
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Diastereomeric Composition of Mongersen Antisense Phosphorothioate Oligonucleotide Preparations and Related Pharmacological Activity Impairment

Abstract: Mongersen is a 21-mer antisense oligonucleotide designed to downregulate Mothers against decapentaplegic homolog 7 (SMAD7) expression to treat Crohn's disease. Mongersen was manufactured in numerous batches at different scales during several years of clinical development, which all appeared identical, using common physicochemical analytical techniques, while only phosphorous-31 nuclear magnetic resonance ( 31 P-NMR) in solution showed marked differences. Close-up analysis of 27 mongersen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Solution 31P-NMR spectroscopy, which has the unique ability to provide information about the chemical environments of the phosphorus atoms, showed that each mongersen preparation had a distinct 31P-NMR profile, indicating that PS chirality was not homogeneous across the batches used in the clinical trials. Principal component analysis helped identify clusters of the batches with similar 31P-NMR spectra, and, interestingly, preparations with the same 31P-NMR spectrum profile had a similar in vitro inhibitory effect of Smad7 [16]. Post hoc analysis of 411 patients enrolled in phase III and receiving mongersen for at least 4 weeks allowed to identify 12 cohorts, each receiving either a single batch (n = 5) or two mixed batches (n = 7) of the active compound (Fig.…”
Section: Mongersenmentioning
confidence: 97%
See 4 more Smart Citations
“…Solution 31P-NMR spectroscopy, which has the unique ability to provide information about the chemical environments of the phosphorus atoms, showed that each mongersen preparation had a distinct 31P-NMR profile, indicating that PS chirality was not homogeneous across the batches used in the clinical trials. Principal component analysis helped identify clusters of the batches with similar 31P-NMR spectra, and, interestingly, preparations with the same 31P-NMR spectrum profile had a similar in vitro inhibitory effect of Smad7 [16]. Post hoc analysis of 411 patients enrolled in phase III and receiving mongersen for at least 4 weeks allowed to identify 12 cohorts, each receiving either a single batch (n = 5) or two mixed batches (n = 7) of the active compound (Fig.…”
Section: Mongersenmentioning
confidence: 97%
“…One-way ANOVA followed by Tukey's post hoc test; batch G vs. batch V/X, * p < 0.05. C Correlation analysis between the mean CDAI score reduction in patients treated with the indicated batches and the ability of such batches to inhibit Smad7 protein expression in vitro (as reported by Arrico et al [16]) [p = 0.0043, Pearson's test coefficient r = 0.8127]. For CD cohorts receiving a mix of two different batches, the in vitro activity was calculated as the mean value of the in vitro activity of the single batches (designated as the percentage of reduction of Smad7/β-actin protein expression vs. control).…”
Section: Mongersenmentioning
confidence: 97%
See 3 more Smart Citations